HUBUNGAN ANTARA PENERAPAN SISTEM KESELAMATAN DAN KESEHATAN KERJA DAN PRODUKTIVITAS PEKERJA PADA PROYEK PEMBANGUNAN GEDUNG DI KABUPATEN SIKKA - Yuyun Inayah; Triapriono Kaidu (Program Studi Teknik Sipil, 2025)
Occupational safety and health are essential considerations in the construction sector. This research aims to assess the impact of safety and health on worker productivity in buiding construction projects in sikka regency. A quantitative approach was employed, with data analysed using descriptive statistics. The respondents for this study were selected through purposive sampling, resulting in a total sample size of 40 participants. The data collection method involved distributing questionnsires directly to the participans. Data analysis utilizes IBM SPSSS Statistics Version 20, which incorporates various techniques, including descriptive statistical tests, validity assessments, reliability evaluations, classical assumption checks, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The research findings show that accupational safety and health do not impact worker productivity in building construction projects in Sikka Regency individualyy and collectively.